(untitled) (Law, State and Telecommunications Review, 2018)
The article introduces this issue of the Law, State, and Telecommunications Review by way of presenting its contents. Statutes, regulations, and judicial decisions of 2017 pertaining to telecommunications are referred to in detail. It also addresses the main political and juridical discussions on the Brazilian telecommunications sector that took place the year before the publication of the journal’s current volume.